'Heart of steel': how trade unions lobby the European Union over emissions trading. Issue 7 (10th November 2021) - Thomas, Adrien
ABSTRACT: This contribution aims to provide a better understanding of trade unions' engagement with climate change policies. It analyses the interactions between intra- and interorganizational bargaining, taking steel trade unions' engagement with the 2018 revision of the EU Emissions Trading System (EU ETS) as a case study. The contribution finds that interorganizational bargaining with employers' organizations strongly influenced the formulation of trade unions' negotiating positions on the EU ETS. This is mainly due to the combination of three factors: the scope EU multilevel decision-making offers each level of trade union action to pursue its interests; trade unions' lack of expertise on climate policies; and the tradition of concession bargaining in the manufacturing industry. By underlining the difficulties faced by trade unions in developing an independent course of action on the EU ETS, the contribution expands our knowledge of the socio-political obstacles to implementing effective emissions reduction policies.